A study on outcome of primary closure versus open fistulectomy in low level fistula in ano - Basa, Maruti; Prakash, Karnati (International Surgery Journal, 2020)
Background: Fistula-in-ano is one of the common ano-rectal disorder which causes appreciable morbidity and inconvenience to the patient. Different surgical techniques have been described in literature from time to time. Open fistulectomy though considered as the standard treatment for fistula in-ano, fistulectomy with primary closure has its merits of short hospital stay, early wound healing and lower costs. The objectives of this study was to compare the period of stay, period of healing, time period to return to daily activities and cost factor between open fistulectomy and primary closure technique. Methods: Patients admitted in all surgical units of NIMRA Hospital, were included in the study without bias on a serial basis. This is a study comprising 50 patients over a period of 12 months from Febrauary 2019 to January 2020. Results: The patients were divided into two equal and comparable groups. Patients who underwent open fistulectomy were classified under Group I and those who underwent fistulectomy with primary closure were classified as Group II. The patient’s characteristics of the two groups were well matched. Conclusions: In patients treated by classical method because of long time taken to heal, number of hospital visits for dressings were more and more antibiotics were prescribed when compared to cases treated by excision of fistula tract and primary closure. From this study it can be concluded that fistulectomy with primary closure is ideal for low anal fistulaures.